2023
DOI: 10.1007/s15010-023-02066-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk of embolic events before and after antibiotic treatment initiation among patients with left-side infective endocarditis

Abstract: Purpose Embolic events (EEs) are a common complication of left-side infective endocarditis (IE). The aim of the present study was to identify risk factors for the occurrence of EEs before or after antibiotic treatment instauration among patients with definite or possible IE. Methods This retro-prospective study was conducted at the Lausanne University Hospital, Lausanne, Switzerland, from January 2014 to June 2022. EEs and IE were defined according to modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the present study among S. aureus bacteremia episodes, OEEs were found in 7%, consistent with previous findings (9%) [ 6 ]. As expected, OEEs were associated with embolic events outside the eye and factors generally linked to systemic embolization, such as large vegetations (≥10 mm), S. aureus , persistent bacteremia/candidemia, and intracardiac abscess [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 71%
“…In the present study among S. aureus bacteremia episodes, OEEs were found in 7%, consistent with previous findings (9%) [ 6 ]. As expected, OEEs were associated with embolic events outside the eye and factors generally linked to systemic embolization, such as large vegetations (≥10 mm), S. aureus , persistent bacteremia/candidemia, and intracardiac abscess [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 71%
“…Epidemiologically, comparing cases from this review ( Supplementary Table 1 ) with data from the institutional IE cohort reveals a higher proportion of intracellular pathogens (40% versus 1–2% in the cohort) and a lower proportion of S. aureus (20% versus 39%) ( 31 ). IE caused by intracellular pathogens typically follows a subacute or chronic course, leading to diagnostic delays due to sterile blood cultures and nonspecific symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…The risk of embolic events in IE is influenced by various factors, including the dimensions of vegetation on the heart valves, specific bacteria such as Staphylococcus aureus, and abscesses or other cardiac complications [ 17 - 19 ]. Notably, vegetation size emerges as a robust predictor of embolic events, with more extensive vegetation (>10 mm) associated with a heightened risk of embolization [ 18 , 19 ]. Early identification of these risk factors assumes paramount importance in the effective management of IE, as it enables clinicians to pinpoint patients who may derive benefit from early surgical intervention to avert further embolization.…”
Section: Reviewmentioning
confidence: 99%
“…Early identification of these risk factors assumes paramount importance in the effective management of IE, as it enables clinicians to pinpoint patients who may derive benefit from early surgical intervention to avert further embolization. Indeed, research indicates that prompt surgical intervention can significantly diminish the incidence of embolic events in IE patients [ 18 , 19 ]. Although the incidence of embolic events in IE exhibits variability across studies, it is generally reported to range between 20% and 40% of cases [ 20 ].…”
Section: Reviewmentioning
confidence: 99%